(untitled) (Música Hodie, 2025)
This article aims to study the digital strategies and online technologies used in creating contemporary piano music in Brazil, China, Japan, and India, as well as represent the Asian and Latin American musical traditions in the digital age. The study was conducted in four stages, focusing on the use of online platforms, virtual instruments, and digital audio workstations (DAWs) in each country. The integration of traditional musical elements with digital technologies was found to be most sophisticated among Chinese respondents, as evidenced by the innovative use of virtual instruments and online collaboration tools. The research perspective is to identify countries that not only impact the development of Brazilian, Chinese, Japanese, and Indian music but also display unique musical elements that affect the specifics of piano music creation.